International finance - Pilbeam, Keith (Palgrave Macmillan, 2006)
The third edition of this internationally renowned and respected text is an ideal introduction to the subject of international finance. Theory is clearly explained and constantly related to the the realities of the modern world economy. The reader is taken through the theories and differing policies of the balance of payments, exchange rates and the international monetary system. Extensive use is made of figures, tables and graphs to illustrate the arguments in the text. It is thoroughly updated and includes a new chapter on the Asian financial crisis.